2022
DOI: 10.1038/s41420-022-00825-9
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SNHG10 upregulates BIN1 to suppress the tumorigenesis and epithelial–mesenchymal transition of epithelial ovarian cancer via sponging miR-200a-3p

Abstract: Epithelial ovarian cancer (EOC) is one of the most frequent and fatal gynecologic malignant tumors resulting in an unsatisfying prognosis. Long non-coding RNAs (lncRNAs) play pivotal roles in the tumorigenesis and progression of EOC. However, the profile of lncRNAs involved in EOC remains to be expanded to further improve clinical treatment strategy. In present study, we identified a novel tumor-suppressive lncRNA small nucleolar RNA host gene 10 (SNHG10) in EOC. Kaplan–Meier analysis and COX proportional haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The expression of SNHG10, which was shown to suppress EMT in epithelial ovarian cancer [ 94 ], was reduced in the Tks4 KO cells, probably resulting in a pro-EMT effect.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SNHG10, which was shown to suppress EMT in epithelial ovarian cancer [ 94 ], was reduced in the Tks4 KO cells, probably resulting in a pro-EMT effect.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has demonstrated that increased cancer cell invasion is associated with EMT-like process. [35][36][37][38] Interestingly, we found that overexpression of SNRPA promoted a transformation from the expression of epithelial markers to mesenchymal markers, indicating that SNRPA promoted the EMT-like process in HCC cells. Herein, we further explored the potential mechanism of SNRPA in the EMTlike process of HCC cells.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, the increased expression of miR-200a-3p was inhibited by BMSC-exos (Supplementary Data, Figure S1), which may contribute to the underlying mechanism and still needs further research. Up to now, these studies found that circRNAs such as circSCMH1 [48], circBACH1 [49], and circST6GALNAC6 [50] and lncRNAs such as lncRNA Gpr137b [51], lncRNA MALAT1 [52], lncRNA SNHG10 [53], and lncRNA TUG1 [54] could reduce the miR-200a-3p expression. In our future research, we will conduct RNA sequencing of BMSC-exos and find which circRNAs or lncRNAs cause miR-200a-3p degradation.…”
Section: Discussionmentioning
confidence: 99%